North-South RandD Spillovers - Helpman, Elhanan (IMF Working Papers; Working Paper, 1994)
We examine the extent to which developing countries that do little, if any, research and development themselves benefit from R and D that is performed in the industrial countries. By trading with an industrial country that has a large 'stock of knowledge' from its cumulative R and D activities, a developing country can boost its productivity by importing a larger variety of intermediate products and capital equipment embodying foreign knowledge, and by acquiring useful information that would otherwise be costly to obtain. Our empirical results, which are based on observations over the 1971-90 period for 77 developing countries, suggest that R and D spillovers from the industrial countries in the North to the developing countries in the South are substantial.